Management an approach to customer expectations - Allen, Gemmy S.; Attner, Raymond F.; Plunkett, Warren R. (South-Western/Cengage Learning, 2013)
A survey of the principles and practices of management as they are being applied in the United States and around the world. It features the effort by managers and organizations to meet or exceed customers' needs and the need organizations and their people have to be guided by effective leadership.